1975
DOI: 10.1007/bf00561533
|View full text |Cite
|
Sign up to set email alerts
|

Statistical association between psoriasis and diabetes: Further results

Abstract: In a group of 200 psoriatic patients from the area of Umbria, Italy, diabetes mellitus occurred in a statistically highly significant association with psoriasis. Similar observations were made earlier in a series of 600 patients. The above correlation also occurred significantly more frequently in patients under 50 years and in male patients. Previous and present experience also demonstrate that psoriasis is statistically correlated with heredity for diabetes and obesity. The possible biological basis of psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 8 publications
4
21
0
Order By: Relevance
“…To determine whether obesity plays a role in the onset of psoriatic arthritis, psoriasis patients with obesity in early life were compared with psoriasis patients without obesity in early life relative to the presence of psoriatic arthritis. Obesity at 18 41) did not increase the likelihood of arthritis within the UPI population. Again, obesity appears to be a consequence of and not a contributor to onset of this variant of psoriasis.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…To determine whether obesity plays a role in the onset of psoriatic arthritis, psoriasis patients with obesity in early life were compared with psoriasis patients without obesity in early life relative to the presence of psoriatic arthritis. Obesity at 18 41) did not increase the likelihood of arthritis within the UPI population. Again, obesity appears to be a consequence of and not a contributor to onset of this variant of psoriasis.…”
Section: Resultsmentioning
confidence: 72%
“…Our study supports previous observations on obesity in psoriasis. [37][38][39][40][41] One report cited that patients with psoriasis are 15% above the average body weight. 37 Another study reported that in a population of 159 200, women with psoriasis were more likely to be obese.…”
Section: Commentmentioning
confidence: 99%
“…Psoriasis patients have been identified as having a higher frequency of hyperlipidemia, depression, hypertension, insulin resistance and diabetes mellitus, and homocysteinemia. 13,[16][17][18][19][20][21][22] Behavioral risk factors, including obesity and smoking, will be discussed in the following section.…”
Section: General Cardiovascular Riskmentioning
confidence: 99%
“…62 Given the increased inflammation seen in patients with psoriasis, it is not surprising that these patients are at an increased risk for meeting criteria of the metabolic syndrome (OR = 1.7-5.3). 9,11,63 Numerous groups have published reports of psoriasis being associated with increased serum insulin levels, 62 diabetes (OR = 1.5-2.5), 5,6,8,9,11,[64][65][66][67][68] hypertension (OR = 1.1-3.3), 5,6,8,9,11,12,65,66,69 hypertriglyceridemia, 9,58-60,63,65 abdominal obesity, 63 or decreased HDL-C. 9,58,59,70 Additionally, hypercholesterolemia, 58,59,65 increased serum LDL-C, 58,59 and generalized hyperlipidemia (OR = 1.3-3.1) 8,11,69 have been reported to be more common in patients with psoriasis. Although the best and greatest amount of evidence supports these associations, it should be noted that a few studies have failed to demonstrate an association between psoriasis and increased insulin, 70 glucose, 63,70 triglycerides, 70 total cholesterol, 60,70 LDL-C, 70 hypertension, 63 or low HDL-C. 60,63 Understanding hormonal and cytokine biology can also ...…”
Section: Links Between Pathogenesis Of Obesity and Psoriasismentioning
confidence: 99%